Changes in agricultural structure, estimated by the scale and substitution effects (1999/2006), in the region of Vale do Ribeira, Brazil - Almeida, L. C. F. [UNESP]; Vargas, P. F. [UNESP]; Tellez, F. A.; Rodriguez, A. M.; Sancho, I. M.; Robinson, M. V.; RuizAltisent, M.; Ballesteros, F. R.; Hernando, ECC (Fundacion General Univ Politecnica Madrid, 2014)
Understanding the phenomena involved in the dynamics of the expansion and contraction of crops areas in a given region is extremely important to the extent that several factors may be involved and may bring socio-economic consequences extremely serious, in case of reduction of agricultural activities affecting the sectors related to this activity or in a situation of expansion of crop areas to replace the existing cultures, which might require shares to which they may be feasible. The Vale do Ribeira, located in the southern state of Sao Paulo (Brazil), comprising 13 municipalities, notably recognized for its low economic activity and agriculture is their main source of income, has shown in recent years major changes in crops areas with important social and economic consequences. The aim of this study was to analyze the evolution of the areas of 26 major agricultural activities in this region in the period of 1996/2006. To verify the change in the composition of the agricultural activities, it was adopted for the determination of the incorporated areas or activities assigned the methodology of the decomposition of the areas in effects of scale and substitution. It was identified changes in the structure of the agricultural area with the reduction measured by the substitution effect of palm areas (Euterpe edulis) at 14,135.10 ha, banana (Musa sp.) at 12,555.10 and black tea (citrus sinensis) to 2,304 ha, total representing more than 70% of the assigned area, with the determinants of the reduction, problems of environmental, phytosanitary, and plant exchange. Alternatively, the results also showed the expansion of areas with activities focused on ornamental plants (1,214.50 ha), peach palm (Bactris gasipaes) in 2,115.60 ha, grass (Zoysia japonica) and mainly formed pastures (3,6019.90 ha). The data confirm empirical observations of a new phase of agricultural activities in the region, given the decline of the banana crop activity / tea and rise of cultivated palm/ornamental plants and pastures.
Keywords: scale effect; substitution effect; agricultural composition